(untitled) (Research, Society and Development, 2022)
Brain abscess is an expansive lesion and most of its manifestations derive from this mass effect on the brain parenchyma. This presentation usually consists of the triad: headache, fever and focal neurological deficits, however, current literature states that this relationship has greater specificity than sensitivity, since most patients do not present the triad at diagnosis. In this direction, it is seen that the alteration in mental status is of greater coherence to the expansive effect of the lesion, being considered a more representative association of the brain abscess. To this extent, neuroimaging techniques are performed in patients who present acute or chronic infectious conditions originating from the possible sources of contamination, associated with a symptomatology with seizures, focal neurological deficits or signs of increased intracranial pressure. Thus, neuroradiological diagnosis distinguishes the lesion that presents as a hypodensity on CT, hypointensity on MRIT1 and hyperintensity on MRIT2 and FLAIR, associated with an enhancing border, characteristic of brain abscess and important in the differential diagnosis.